Cultural Pluralism through Translation? Imagining the Italian Other in the Habsburg Monarchy - Wolf, Michaela (TTR)

(untitled) (Association canadienne de traductologie, 2001)
AbstractThe historical relationships between the Italian peninsula and Austria are also reflected in the reception of Italian literary production in the Habsburg monarchy. This can be seen in the formation of a literary canon which always goes together with selective mechanisms. These selections decisively contribute to the formation of cultural hegemonies.This paper presents the creation of the Other through the activity of translation in the context of the reception of national Italian literature in the Habsburg Monarchy. It will analyze what was accepted on the cultural market of the Habsburg Monarchy and what the criteria for the reception of translated Italian literature were. Against the background of a short survey of the various aspects of the Italian image created through intercultural contacts, this paper investigates the ways in which these images were discussed, created and represented through translation. The analysis of some paratexts will show that the margin left for the Italian cultural Other was quite narrow and largely reduced to stereotypical views of Italian culture.